2005
DOI: 10.1007/s10450-005-5988-2
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Assisted Simulated Moving Bed Systems

Abstract: The principles of simulated moving bed (SMB) and thermal swing adsorption (TSA) are combined to develop a traveling wave mode, thermally assisted SMB. The four-zone, thermal SMB and the corresponding one-column, thermal Analog to the SMB are studied for separating binary systems with linear isotherms. Design parameters and operating conditions are determined using the local equilibrium theory and detailed simulations are done with the commercially available chromatography/SMB software package Aspen Chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 5 publications
(7 reference statements)
0
24
0
Order By: Relevance
“…One is to express both q s and b as a function of temperature, while the other is to express only b as a function of temperature. Between the two, the latter has been the most accepted approach in the area of temperature-gradient separation process development. It has also been widely adopted in other areas. Furthermore, the latter approach is more faithful to the fundamental theory of the Langmuir model, which is based on the principle that the saturation capacity ( q s ) must be independent of temperature . Therefore, the latter approach will be used in this study.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…One is to express both q s and b as a function of temperature, while the other is to express only b as a function of temperature. Between the two, the latter has been the most accepted approach in the area of temperature-gradient separation process development. It has also been widely adopted in other areas. Furthermore, the latter approach is more faithful to the fundamental theory of the Langmuir model, which is based on the principle that the saturation capacity ( q s ) must be independent of temperature . Therefore, the latter approach will be used in this study.…”
Section: Theorymentioning
confidence: 99%
“…It was also found from the measured adsorption equilibrium data that the adsorption affinity of each acid to Amberchrom CG300C was largely affected by temperature. This indicates that the design of a temperature-gradient SMB process, which was reported to surpass a classical SMB in separation performance, is also practicable. Finally, the thermodynamic properties of the system under investigation were estimated, which revealed that the adsorption of each acid onto Amberchrom CG300C was exothermic and belonged to the case of physisorption.…”
Section: Introductionmentioning
confidence: 99%
“…These two parameters ( q s and K L ) are called the Langmuir model parameters. In regard to the temperature dependences of the Langmuir model parameters, it is widely accepted in the area of adsorption separation process development that only K L is affected by temperature, while q s is independent of temperature. …”
Section: Resultsmentioning
confidence: 99%
“…In the previous section, the Langmuir model parameters were determined at three discrete temperatures (Table ). This can sometimes be a barrier to the immediate application of the Langmuir model to the design or simulation of a temperature-gradient chromatographic process, where the process temperature is usually allowed to undergo continuous variation along the axial distance. , In this case, it would be more efficient to utilize the Langmuir model expressed as a continuous function of temperature. Such a temperature-modulated model that can account for the adsorption data in Table is described in this section.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, three new operation strategies for SMB have been suggested. One strategy is the direct manipulation of adsorption equilibria by a supercritical fluid,1, 2 a solvent gradient,3, 4 or a temperature gradient 5, 6. The second strategy is to combine a conventional SMB unit with an additional separation step.…”
Section: Introductionmentioning
confidence: 99%